Information skills programs : implementation and evaluation - Sinnasamy, J. (University of Malaya Library, 2006)

(untitled)
The information skills programs at academic libraries aim to produce students with competent information seeking behavior. This means that students will be aware of their needs for information, know where the information is, how to retrieve and use them effectively for learning and research. The ultimate objective is to enable students to be information literate. However, librarians work independently without much collaboration with the faculties. Library information skills programs are usually evaluated as useful by the students. How much the students use the strategies learnt in these programs for their learning and research is difficult for the librarians to gauge. On the other hand, the faculties deal closely with the students and so are in a better position to measure their performance. Librarians should aim to initiate a partnership between the faculty courses and the information skills programs. Similarly, academics should be aware of the impact Information Skills Programs have on the students and encourage students to participate in these programs and encourage the use of library resources for their assignments and project papers. This paper discusses the relationship between the course contents of Information Skills Programs and information literacy.